Research advances in nanomaterials with aromatic functional groups for the treatment of inflammatory bowel disease - He, Juan; Guo, Hong; Zou, Min (Frontiers in Bioengineering and Biotechnology, 2025)
Inflammatory bowel disease (IBD) is a group of chronic, non-specific intestinal inflammatory diseases. The treatment of IBD focuses on alleviating intestinal inflammation. However, traditional drug treatment methods are limited by the side effects of systemic therapy, poor targeting of oral administration, and low bioavailability at the site of inflammation. Fortunately, the application of nanomaterials in the intestine is expected to alleviate these problems. Nanomaterials have unique physicochemical properties and can be used for targeted drug delivery through the mucus layer. Moreover, they can also be engulfed by macrophages through endocytosis, thereby regulating the immune environment of the intestine and potentially altering drug properties. In addition, nanomaterials can be divided into organic nanomaterials and inorganic nanomaterials according to their properties. The functional groups in organic nanomaterials directly determine the characteristics and effects of these materials. Among them, aromatic rings enhance drug stability, improve drug solubility and targeting, and exert anti-inflammatory, antioxidant, and immunomodulatory effects, which are conducive to the innovation of IBD treatment. This paper focuses on the role of aromatic rings, briefly describes the current therapeutic status of organic nanomaterials in inflammatory bowel disease, and discusses the deficiencies of existing research as well as directions for future studies. This paper provides insights into understanding the influence of functional groups on nanomaterials.